Cellular and Transcriptional Responses of Resistant and Susceptible Cultivars of Alfalfa to the Root Lesion Nematode, Pratylenchus penetrans - Vieira, Paulo; Mowery, Joseph; Eisenback, Jonathan D.; Shao, Jonathan; Nemchinov, Lev G. (Frontiers in Plant Science, 2019)
The root lesion nematode (RLN), Pratylenchus penetrans, is a migratory species that attacks a broad range of crops, including alfalfa. High levels of infection can reduce alfalfa forage yields and lead to decreased cold tolerance. Currently, there are no commercially certified varieties with root lesion nematode resistance. Little information on molecular interactions between alfalfa and P. penetrans, that would shed light on mechanisms of alfalfa resistance to RLN, is available. To advance our understanding of the host-pathogen interactions and to gain biological insights into the genetics and genomics of host resistance to RLN, we performed a comprehensive assessment of resistant and susceptible interactions of alfalfa with P. penetrans that included root penetration studies, ultrastructural observations, and global gene expression profiling of host plants and the nematode. Several gene-candidates associated with alfalfa resistance to P. penetrans and nematode parasitism genes encoding nematode effector proteins were identified for potential use in alfalfa breeding programs or development of new nematicides. We propose that preformed or constitutive defenses, such as significant accumulation of tannin-like deposits in root cells of the resistant cultivar, could be a key to nematode resistance, at least for the specific case of alfalfa-P. penetrans interaction.